Case studies in stroke: common and uncommon presentations - Hennerici, Michael G. (Cambridge University Press, 2007)
Neurologists learn from their patients, and this selection of 60 stroke cases will inform and challenge clinicians at all stages in their careers. Including both common and unusual cases, the aim is to reinforce diagnostic skills through careful analysis of individual presenting patterns, and to guide treatment decisions. Each case consists of a clinical history, examination findings and special investigations, usually involving imaging before a diagnosis is given. There then follows for each case a discussion of the clinical issues raised by the case, in which the main teaching points are emphasized. Selected references, frequently including the first description, are provided at the conclusion of each case. Drawing on the expertise of leading teachers and practitioners, and liberally illustrated, these case studies and the discussions that accompany them are an essential guide to learning the complexity of stroke diagnosis